(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Minarsih S, Hanudin E, Nurudin M. 2021. The earthworm’s diversity and their relationship to the soil physicochemical properties under the stands of perennial plant at the Mount Merapi forest, Yogyakarta, Indonesia. Biodiversitas 22: 3237-3244. The study was to propose earthworm as bioindicator and its correlation to the soil physicochemical properties underneath some perennial plants. Soil samples and earthworm observation was taken out at a depth of 0-10 cm and 10-20 cm under the stands of Acacia decurrens, coffee, Albizia chinensis, bamboo, snake fruit, and Acacia mangium. Soil moisture, temperature and Physico-chemical properties were measured, such as texture, pH, organic C, mineralized C, total N, mineralized N, available P, and base cations (Ca, Mg, K, Na). The results revealed that the earthworms density underneath of the stands of coffee was 105.4 ind.m-2 > snake fruit 92.6 ind.m-2 > Albizia chinensis 66.7 ind.m-2 > A. decurrens ? bamboo 40.7 ind.m-2 > A. mangium 37.0 ind.m-2. The dominant species of the earthworms found at a depth of 0-10 cm consisted of four species, namely: Pheretima hamayana, Pheretima californica, Eudrillus eugeniae, and Eiseniella tetraeda. Meanwhile, the earthworms diversity underneath the stands of coffee was H’=1.26 > A. mangium H’=1.03 > Albizia chinensis H’=0.69 > ?H’=0.69 > bamboo H’=0.59. The soil physicochemical properties was positively correlated to the earthworms density was C-mineralized (r = 0.823) ? soil moisture (r = 0.585) ? available K (r = 0.529) ? available Ca (r = 0.505) ? available Mg (0.494). The results could be concluded that labile organic carbon, water, and alkaline cations were the important factors in improving soil biological fertility in the active volcano area.